Fracture Outpatients Characteristics of West Java Province Occupational Health Hospital (RSUD-KK) in 2024 - Raden Shofia Safitri; Ayu Prawesti Priambodo; Sheizi Prista Sari (JURNAL CITRA KEPERAWATAN, 2026)
Fracture is the medical term for broken bones. Fractures often occur as a result of motor vehicle accidents and workplace accidents. With the increasing number of incidents, the data recording of fracture incidents in Indonesia remains suboptimal. This study aims to determine the fracture patient characteristics at the Outpatient Unit of the West Java Occupational Health Hospital in 2024. This study employs descriptive quantitative analysis of secondary data from orthopedic outpatient medical records. 196 samples met the criteria for completeness of research variables. Additional supporting data was also obtained from the West Java Health Office. The majority of patient characteristics were in the 18-44 age group (39.3%), female (58.16%), BPJS users (87.2%), and non-workers (65.8%). The most common fracture locations were the upper extremities (61.7%) (radius: 27.6%), and the lower extremities (29.6%), (femur: 8.2%). The dominant classification was closed fractures and uncategorized conditions. The majority of therapies were analgesics (66.3%). The dominant complications were neglect and malunion. The diversity of fracture patient characteristics was influenced by mobility and bone strength. Analgesics were the primary choice for pain management. This study is expected to be a reference for more comprehensive research and a source of data for hospital policy development. Keywords: Fracture, Fracture Complications, Fracture Therapy, Patient Characteristics